Hubungan Culture Shock dengan Penyesuaian Diri Mahasiswa Baru yang Berasal dari Luar Sumatera Barat di Program Studi Bimbingan dan Konseling UIN Sjech M. Djamil Djambek Bukittinggi - Wahyuni, Lidya; Afrida, Yeni (YASIN, 2024)
The difficulty of adapting experienced by students of UIN Sjech M. Djamil Djambek Bukitinggi, especially those from outside West Sumatra, is predicted to be caused by culture shock. The purpose of the study was to determine the relationship between culture shock and self-adjustment of new students from outside West Sumatra in the Guidance and Counseling Study Program. The type of quantitative research with correlation analysis techniques. The sample was all students outside West Sumatra, Guidance and Counseling Study Program, class of 2023, totaling 40 students. The sampling technique used the total sampling technique. The research instrument was a questionnaire modified by the researcher. To see the relationship between culture shock and self-adjustment of UIN Sjech M. Djamil Djambek Bukittinggi, the researcher used the Product Moment Test. The results of the study showed a significant relationship between culture shock and self-adjustment. This is indicated by a negative r value of -.375 at the r value and a significant value of p 0.017 <0.05. This states that the hypothesis is accepted so that it can be concluded that there is a negative relationship between culture shock and self-adjustment in new students class of 2023 in the Guidance and Counseling Study Program, UIN Bukittinggi. The level of culture shock experienced by new students of the 2023 intake in the Guidance and Counseling Study Program at UIN Bukittinggi is 6 students in the high category (15.0%), 28 students in the medium category (85.0%), and 6 students in the low category (15.0%). Meanwhile, the level of self-adjustment of new students of the 2023 intake in the Guidance and Counseling Study Program at UIN Bukittinggi is 4 students in the high category (10.0%), 27 students in the medium category (67.5%), and 9 students in the low category (22.5%).